Evaluation of direct analysis in real time ionization-mass spectrometry (DART-MS) in fish metabolomics aimed to assess the response to dietary supplementation - Cajka, Tomas; Danhelova, Hana; Vavrecka, Antonin; Riddellova, Katerina; Kocourek, Vladimir; Vacha, Frantisek; Hajslova, Jana (Talanta, 2013)
Ambient mass spectrometry employing a direct analysis in real time (DART) ion source coupled to a medium high-resolution/accurate mass time-of-flight mass spectrometer (TOFMS) was used as a rapid tool for metabolomic fingerprinting to study the effects of supplemental feeding with cereals (triticale) on the composition of muscle metabolites of common carp (Cyprinus carpio L.). First, the sample extraction and DART-TOFMS instrumental conditions were optimized to obtain the broadest possible representation of ionizable compounds occurring in the extracts obtained from common carp muscle. To this end, a simultaneous (all-in-one) extraction procedure was developed employing water and cyclohexane mixture as the extraction solvents. Under these conditions both polar as well as non-polar metabolites were isolated within a single extraction step. Next, the metabolomic fingerprints (mass spectra) of a large set of common carp muscle extracts were acquired. Finally, the experimental data were statistically evaluated using principal component analysis (PCA) and orthogonal partial least squares discriminant analysis (OPLS-DA). Using this approach, differentiation of common carp muscle in response to dietary supplementation (feeding with and without cereals) was feasible. Correct classification was obtained based on the assessment of polar and as well as non-polar extracts fingerprints. The current study showed that DART-TOFMS metabolomic fingerprinting represents a rapid and powerful analytical strategy enabling differentiation of common carp muscles according to feeding history by recording metabolomic fingerprints of ionizable components under the conditions of ambient MS.
Keywords: analýza hlavních komponent; Water; Carps; Muscle, Skeletal; Metabolomic fingerprinting; extrakce kapalina-kapalina; Mass spectrometry; voda; Direct analysis in real time (DART); potravní doplňky; metabolom; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Cyclohexanes; Liquid-Liquid Extraction; Principal Component Analysis; Metabolome; dieta; Solvents; Diet; metoda nejmenších čtverců; zvířata; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Dietary Supplements; Least-Squares Analysis; Feeding; kapři; Animals; Fish; Edible Grain; kosterní svaly; rozpouštědla; jedlá semena; cyklohexany